Open Source Software and Schools: New Opportunities and Directions - Gary Hepburn (The Canadian Network for Innovation in Education (CNIE), 2005)
Abstract: Integrating information and communication technology into schools has been challenging. A central component of the challenge is coping with the expense and usage restrictions of software that is installed on school computers. An alternative approach to the educational software problem is, however, emerging. This approach involves making greater use of open source software. In many cases open source software can effectively replace the proprietary or commercial software that dominates the educational computing landscape. Using this software option would result in decreased costs, increased flexibility, and increased opportunities to address social and ethical issues related to information and communication technology. In order to responsibly spend taxpayers' money and to maximize the potential of information and communication technology in education, it is important that educators learn about open source software and challenge conceptions that give priority to proprietary software.